Anterior Lumbar Interbody Fusion With Cage Retrieval for the Treatment of Pseudarthrosis After Transforaminal Lumbar Interbody Fusion. (16th November 2020) - Safaee, Michael; Tenorio, Alexander; Haddad, Alexander F; Wu, Bian; Hu, Serena; Tay, Bobby; Burch, Shane; Berven, Sigurd; Deviren, Vedat; Dhall, Sanjay S; Chou, Dean; Mummaneni, Praveen V; et al.
Abstract: INTRODUCTION: The treatment of pseudarthrosis after transforaminal lumbar interbody fusion (TLIF) can be challenging, particularly when anterior column reconstruction is required. There are limited data on TLIF cage removal through an anterior approach. METHODS: ALIFs performed at a single academic medical center were reviewed to identify cases performed for the treatment of pseudarthrosis after TLIF. Patient demographics, surgical characteristics, perioperative complications, and 1-year radiographic data were collected. RESULTS: Eighty-four patients were identified with mean age of 59 years and 37 women (44.0%). Sixteen patients (19.0%) underwent removal of two interbody cages for a total of 99 implants removed with distribution as follows: 1 L2/3 (0.9%), 6 L3/4 (5.7%), 37 L4/5 (41.5%), 55 L5/S1 (51.9%). There were two intraoperative venous injuries (2.4%) and 21 postoperative complications (25.0%) in a total of 22 patients. Postoperative complications were as follows: 7 ileus (8.3%), 5 wound-related (6.0%), 1 rectus hematoma (1.1%), and 12 medical complications (14.3%), including 6 pulmonary (7.1%), 3 cardiac (3.6%), and 6 urinary tract infections (7.1%). Among 58 patients with at least 1-year follow-up, 56 (96.6%) had solid fusion. There were 5 cases of subsidence (6.0%), none of which required surgical revision. Two patients (2.4%) required additional surgery at the level of ALIF for pseudarthrosis. CONCLUSION: ALIF is a safe and effective technique for the treatment of TLIF cage pseudarthrosis with a favorable risk profile.